ENRICH: A promising oncology nurse training program to implement ASCO clinical practice guidelines on fertility for AYA cancer patients. Issue 11 (November 2016) - Vadaparampil, Susan T.; Gwede, Clement K.; Meade, Cathy; Kelvin, Joanne; Reich, Richard R.; Reinecke, Joyce; Bowman, Meghan; Sehovic, Ivana; Quinn, Gwendolyn P.; ,
Highlights: ENRICH improved nurses' knowledge of fertility needs for AYA oncology patients. ENRICH increased nurses' involvement in fertility-related activities. ENRICH provides a model for training nurses to integrate fertility in oncology care. Abstract: Objective: We describe the impact of ENRICH (Educating Nurses about Reproductive Issues in Cancer Healthcare), a web-based communication-skill-building curriculum for oncology nurses regarding AYA fertility and other reproductive health issues. Methods: Participants completed an 8-week course that incorporated didactic content, case studies, and interactive learning. Each learner completed a pre- and post-test assessing knowledge and a 6-month follow-up survey assessing learner behaviors and institutional changes. Results: Out of 77 participants, the majority (72%) scored higher on the post-test. Fifty-four participants completed the follow-up survey: 41% reviewed current institutional practices, 20% formed a committee, and 37% gathered patient materials or financial resources (22%). Participants also reported new policies (30%), in-service education (37%), new patient education materials (26%), a patient navigator role (28%), and workplace collaborations with reproductive specialists (46%). Conclusion: ENRICH improved nurses' knowledge and involvement in activities addressing fertility needs of oncology patients. Our study provides a readily accessible model to prepare oncology nurses to integrate American Society of Clinical Oncology guidelines and improve Quality Oncology Practice Initiative measures related to fertility. Practice implications: Nurses will be better prepared to discuss important survivorship issues related to fertility and reproductive health, leading to improved quality of life outcomes for AYAs.